1990
DOI: 10.1210/endo-126-3-1457
|View full text |Cite
|
Sign up to set email alerts
|

The Proliferative Effect of “Anti-Androgens” on the Androgen-Sensitive Human Prostate Tumor Cell Line LNCaP

Abstract: The effect of steroidal and nonsteroidal "anti-androgens" on the proliferative capacity of androgen-sensitive LNCaP-FGC human prostate tumor cells in culture was studied using charcoal-dextran stripped human serum-supplemented media. Cyproterone and medroxyprogesterone acetates, flutamide, hydroxyflutamide, and anandron (R23908) were administered alone at concentrations between 3 X 10(-12) and 3 X 10(-6) M. Results indicated that although medroxyprogesterone induced maximal proliferation at 3 X 10(-9) M, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 21 publications
3
46
0
Order By: Relevance
“…These cells may respond to androgen/AR signals differentially depending on different environments (Olea et al, 1990) and exhibited variants. For example, the ARexpressing LNCaP-FGC and LNCaP-LNO cell lines isolated from the same lymph node metastatic tumor (Horoszewicz et al, 1983) exhibited different and opposite proliferation responses toward androgen (Olea et al, 1990, Soto et al, 1995. Proliferation of LNCaP-FGC cells was stimulated by a low concentration and suppressed by a high concentration of androgen, whereas proliferation of LNCaP-LNO cells was suppressed by physiological concentrations of androgen.…”
Section: Lncap Cells: Ar Could Function As Proliferation Stimulator Amentioning
confidence: 99%
“…These cells may respond to androgen/AR signals differentially depending on different environments (Olea et al, 1990) and exhibited variants. For example, the ARexpressing LNCaP-FGC and LNCaP-LNO cell lines isolated from the same lymph node metastatic tumor (Horoszewicz et al, 1983) exhibited different and opposite proliferation responses toward androgen (Olea et al, 1990, Soto et al, 1995. Proliferation of LNCaP-FGC cells was stimulated by a low concentration and suppressed by a high concentration of androgen, whereas proliferation of LNCaP-LNO cells was suppressed by physiological concentrations of androgen.…”
Section: Lncap Cells: Ar Could Function As Proliferation Stimulator Amentioning
confidence: 99%
“…Androgens are considered to play a crucial role in the development and progression of prostate cancer, since men castrated before puberty do not develop this disease (11). Moreover, antiandrogens inhibit prostate growth in vitro (12) and in vivo (13). It is also known that, testosterone is irreversibly converted to dihydrotestosterone (DHT) within the prostate gland by the 5-␣a-reductase enzyme, and that DHT is the active androgen in the prostate (14).…”
mentioning
confidence: 99%
“…It is believed that LNCaP cells gain flutamide resistance by AR mutation (T877A). In 1990, Olea et al [13] reported that flutamide at concentrations of 3 9 10 -8 M or higher was effective in inducing proliferation of LNCaP-FGC cells. However, they did not mention the time of hydroxyflutamide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The second is flutamide's shutoff effect. Olea et al [13] reported that anti-androgens did not trigger a proliferative shutoff response, whereas androgens do. Furthermore, dihydrotestosterone may act on the LNCaP cells synergistically with hydroxyflutamide in stimulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%